2019
DOI: 10.1159/000500516
|View full text |Cite
|
Sign up to set email alerts
|

Severe Complications from an Unexpectedly High Serum Mycophenolic Acid Concentration in a Patient with Renal Failure Secondary to Lupus Nephritis: A Case Report

Abstract: Mycophenolate mofetil (MMF) is used widely to treat lupus nephritis and is considered safer than other immunosuppressive drugs. Reports on severe complications related to MMF are sparse. We report a case of a patient with lupus nephritis in whom severe complications were possibly caused by MMF. The patient was a 17-year-old girl who received a diagnosis of lupus nephritis at the age of 14 years and had been taking steroid and immunosuppressive agents since then. One week after starting MMF 1 g/day instead of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A case report by Doi et al reported seizures, leukopenia, thrombocytopenia, and acute renal failure in a 17-year-old girl with lupus nephritis who took 1 g of MMF daily for one week. But her symptoms resolved in a few weeks without complications after the discontinuation of the drug [ 10 ]. In a 40-year-old female kidney recipient under maintenance dose of MMF, acute ingestion of 25 g of MMF resulted in moderate leukopenia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case report by Doi et al reported seizures, leukopenia, thrombocytopenia, and acute renal failure in a 17-year-old girl with lupus nephritis who took 1 g of MMF daily for one week. But her symptoms resolved in a few weeks without complications after the discontinuation of the drug [ 10 ]. In a 40-year-old female kidney recipient under maintenance dose of MMF, acute ingestion of 25 g of MMF resulted in moderate leukopenia [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of MMF caries the risk of being deliberately misused by patients for self-harms and, if trough concentrations are not measured on a regular basis, may lead to intoxication even on recommended doses. 9 In severe acute overdose situations, expected events would be GI problems, leukopenia, anemia, and thrombocytopenia and if long-lasting, possible overimmunosuppression leading to increased susceptibility to infections. With timely withdrawal of additional MMF/EC-MPS doses, rapid initiation of EHC inhibiting therapy, it is possible to reduce and sometimes avoid excessive bone marrow depression, and other adverse outcomes may be minimized.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms were initially thought to be lupus related but turned out to be due to severe MPA intoxication with a measured concentration of 88 mg/L. 9 The patient experienced a complete recovery without any complications after MMF withdrawal.…”
Section: Introductionmentioning
confidence: 98%
“…MCD may cause multiple lymph nodes enlargement and organs dysfunction 2 . Approximately 50% of patients with MCD who are negative for HIV and HHV8 comprise a subgroup that has been termed as idiopathic MCD (iMCD) 3 . As a particular subtype of iMCD, TAFRO syndrome was extremely rare to be reported, which was characterized by thrombocytopenia [T], anasarca [A], fever [F], renal failure [R], and organomegaly [O].…”
Section: Introductionmentioning
confidence: 99%